Modern Seminary Education Management to Support SDG 4: A Case Study of Seminari Petrus Van Diepen, Southwest Papua - Imanuel Tenau; Erny Roesminingsih; Karwanto Karwanto (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To analyzes the situational leadership styles of boarding school principals in improving school achievement at Senior High School Katolik Villanova and Senior High School Katolik Santo Arnoldus Janssen. Method: A qualitative multi-site study was employed. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using an interactive model involving data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation. Results: The findings reveal that principals applied flexible situational leadership styles directing, coaching, supporting, and delegating according to teachers’ and staff members’ readiness. Leadership extended beyond academic management by integrating character formation, discipline, faith development, and community life, resulting in improved academic and non-academic achievement, teacher professionalism, and a collaborative school climate. Novelty: Proposesing a spiritually oriented situational leadership model that integrates faith formation, moral exemplarity, and pastoral practices into educational leadership. The model contributes to SDG 4 (Quality Education) by promoting holistic and character-based education and supports SDG 16 (Peace, Justice and Strong Institutions) through ethical leadership and values-based educational governance in Catholic boarding schools.